Public Services in the Era of Digitalization: Effectiveness of SIMANIZ Application Innovation in Local Government Scope - Musta'ana; Septi Wulandari; Esa Septian; Manuel Ximenes (Universitas Merdeka Malang, 2025)
Licensing Management (SIMANIZ) in supporting the quality of public services at DPMPTSP Bojonegoro Regency. This research uses a quantitative approach with survey techniques on 100 respondents of the service user community. A total of 15 service attributes were used to evaluate the performance and level of importance of services, which were then analyzed using the (IPA) method. The results showed that the majority of attributes were in a strategic position with high performance and importance values. This finding indicates that the SIMANIZ application has played a role in improving the speed, efficiency, and accessibility of public services. However, some attributes are in priority areas for evaluation, especially related to service speed and continuity of system development. This study recommends the need for continuous improvement of service features that are considered important by the community in order to achieve digital services that are effective, adaptive, and oriented to the needs of service users.